Composição de rotífera em corpos d'água da bacia do rio Tietê São Paulo, Brasil - Lucinda, Irene (2003)
Rotifera composition in four Units of Management of Water Resources of Tietê River, in São Paulo State, was studied. Samples were obtained using a 35µm plankton net pulled, horizontally and vertically, through limnetic and littoral regions and, afterwards, fixed with 4% formalin. One hundred and ninety nine taxa were identified. These belong to 23 families of subclass Monogononta. The families Lecanidae, Brachionidae, Trichocercidae, Notommatidae, Lepadellidae and Testudinellidae, commons in tropical environments, are best represented. Keratella cochlearis, Lecane bulla, Polyarthra aff. vulgaris and bdelloids are present in almost all localities sampled. Lecane bulla, Lecane closterocerca, Colurella uncinata f. bicuspidata and genera Euchlanis occurred preferentially in littoral, among the macrophytes. There isnt relation between richness of Rotifera and limnology variables associated to trophic status of water. Others environmental components must be investigate. The occurrence and/or dominance of some species seem to be associated to high trophic status of water, per example: genera Brachionus, Pompholyx and Anuraeopsis and species Filinia opoliensis, Kellicottia bostoniensis, Keratella cochlearis var. tecta, K. tropica, K. lenzi lenzi and Trichocerca capucina multicrinis. The high dominance of Conochilus unicornis seems to be associated to waters of lawest trophic status. Almost all the reservoirs seem to have less similarity on the Rotifera fauna due to the occurrence of almost rare and/or casual species. Thirty one new occurrences for São Paulo State, including four new for Neotropical Region, are recorded.